Could enterprise risk management (ERM) enhance shareholders' wealth?: The lesson from credit crunch - Kasim M.A.B.; Hanafi S.R.B.M.; Aziz A.A.; Kasim I.B. (Nova Science Publishers, Inc., 2023)
The primary research objective of this paper is to provide a review of literature concerning the implementation of the ERM. The issue surrounding the implementation of the ERM in relation to the credit crisis creates awareness on the viability of the ERM in preserving shareholders' wealth. This paper also highlights the evolution, forces, benefits and challenges in the ERM implementation. The linkages between ERM and organizational governance incorporate the impact towards financial performance. The paper suggested few future studies that could significantly contribute to the overall risk management literature. 2012 by Nova Science Publishers, Inc. All rights reserved.